Plan d’Investissement pour une Agriculture Intelligente face au Climat (AIC) au Sénégal - Chabot, Philippe; Siagbe, Golli; Ouedraogo, Issa; Jalango, Dorcas; Dieye, Bounama; Diagne, Djibril; Diop, Mbaye; Sow, Fafa; Coumba, Ndeye; Mbengue, Maty; Vyas, Shalika; Wamicwe, Peter; et al. (2024)
Senegal, a Sahelian country in West Africa, relies heavily on agriculture, which contributes 17% of GDP and sustains over half the rural population. However, climate change poses significant challenges, including rising temperatures, reduced precipitation, and soil degradation, threatening agricultural productivity and livestock systems. To address these challenges, Senegal has developed the Climate-Smart Agriculture Investment Plan (PIAIC), an inclusive strategy aligned with national and international frameworks such as the Paris Agreement and the SDGs. The PIAIC prioritizes seven investments across three strategic axes: sustainable resource management, improved agricultural and livestock systems, and enhanced post-harvest practices and market access. These initiatives aim to strengthen resilience, boost productivity, and reduce greenhouse gas emissions, ensuring a sustainable agricultural future for Senegal. Backed by a CFA 114.5 billion budget, the PIAIC represents a transformative step toward climate-resilient and food-secure agriculture.